Effect of Dynamic Window Opening Behaviors on Indoor Thermal Environment and Energy Consumption in Residential Buildings of Different Chinese Thermal Climate Zones - Fangpeng Guo; Zhenqian Chen; Jun Wang (Buildings)
Residential occupant window opening behavior has a significant impact on building design optimization, energy consumption diagnosis, performance evaluation and energy simulation. However, there has not been much research quantifying the evaluation of window opening behaviors’ influence with respect to residential thermal comfort and HVAC energy for different thermal climate zones in China. Therefore, this paper compared the impacts of six window opening models on HVAC energy consumption and thermal comfort in residential buildings across five thermal climate zones in China through a series of simulation tests using a building performance simulation software. The results indicated that in terms of thermal comfort, the optimal window opening model is WOM-3 (the window opening model based on outdoor air temperature) for Shenyang, Beijing, Wuhan, and Guangzhou, with thermal comfort hours of 2076, 2065, 2244, and 3491, and WOM-6 (the window opening model based on occupant window opening schedules) was optimal for Kunming with thermal comfort hours of 3292. With respect to HVAC energy consumption, the window opening models WOM-3, WOM-4 (the window opening model based on 15 ≤ Tout ≤ Tin ≤ 28), and WOM-6 (the window opening model based on outdoor air temperature Coupled 15 ≤ Tout ≤ 28 and the occupant window opening schedules) were found to be optimal for Shenyang, Beijing, Wuhan, Guangzhou, and Kunming. When taking thermal comfort and HVAC energy into consideration, the outdoor air temperature-based WOM-3 is the ideal window opening model. Moreover, the optimal window opening model for each month has been elucidated.